IFRS adoption and firms’ opacity around the world: what factors affect this relationship? - Mongrut, Samuel (2021)
Purpose. This paper aims to identify what are the moderating factors affecting the relationship between firms’ adoption of international financial and reporting standards (IFRS) and the firm’s opacity. Design/methodology/approach. This study uses the meta-analysis methodology from Hunter et al. (1982) to find if the mere IFRS adoption reduces firm’s opacity and a meta-regression from Stanley and Jarrell (1989) to identify the moderating factors that may influence this relationship. Findings. Contrary to previous studies, this study finds a low, negative and nonsignificant correlation between IFRS adoption and firms’ opacity, but this relationship depends on the geographical region. Using 34 results from 28 studies from different continents published between 2005 and 2018 this study finds that IFRS adoption reduces opacity in countries with common law (COML) and with more authorities’ oversight and power to enforce the rules. Originality/value. This study finds two institutional commonalities between different previous studies that intend to assess the impact of the IFRS adoption upon firms’ opacity: the legal system and the authorities’ oversight power.